Identification of a control-oriented energy model for a system of fan coil units. (October 2019) - Martinčević, Anita; Vašak, Mario; Lešić, Vinko
Abstract: In recent years, application of advanced control, fault detection and diagnosis algorithms for building heating and cooling systems has been intensively investigated with the aim to improve their energy efficiency and bring the buildings sector into the smart city arena. Hindering the trend, hysteresis and proportional–integral–derivative controllers are still a common practice for temperature control in buildings with Fan Coil Units (FCUs). Introduction of more sophisticated controllers for additional savings requires a cost-effective approach for identification of an energy model which accurately resembles thermal and hydraulic performance of a system of FCUs. In the present work, the control-oriented energy model of a system of FCUs is developed and accompanied with replicable, robust and simple methodologies for its identification derived by consolidating the advantages of physical modelling, identification methods and manufacturer's catalogue data. The validity of the developed approach is tested on the 248-office living-lab. The introduced simple and accurate dynamic characterization of energy transmitted from a FCU to zone air fills the gap between thermal and energy management for buildings. This enables implementation of predictive building controls and unleashes significant energy and cost-saving potentials of a smart building in a smart city.